Intracardiac Echocardiography to Diagnose Bioprosthetic Pulmonary Valve Thrombosis - DeZorzi, Christopher J. (JACC Case Rep, 2021)
A 48-year-old woman presented with heart failure and bioprosthetic pulmonary valve regurgitation 2 years after pulmonary valve replacement. Intracardiac echocardiography demonstrated uniform thickening of a single prosthetic valve leaflet suggesting leaflet thrombosis rather than bioprosthetic valve degeneration. After 3 months of anticoagulation, valve regurgitation and symptoms improved. (Level of Difficulty: Intermediate.)